Experiences in the use of thin-layer nuclear densimeters - Rodríguez, Marcos (2025)
This article presents some experiences regarding the use of thin layer nuclear densimeters in road maintenance projects in Costa Rica. Road maintenance programs in Costa Rica must begin with basic road maintenance activities, such as drainage and vegetation cleaning, pothole repair, and the restoration of severely damaged surface areas. In these projects, the fundamental task was the construction of patches in asphalt pavements with high levels of quality, both in the mixture used and in the repair procedures.